Differences in Work-Related Adverse Events by Sex and Industry in Cases Involving Compensation for Mental Disorders and Suicide in Japan From 2010 to 2014. Issue 4 (April 2018) - Yamauchi, Takashi; Sasaki, Takeshi; Yoshikawa, Toru; Matsumoto, Shun; Takahashi, Masaya; Suka, Machi; Yanagisawa, Hiroyuki
Abstract : Objective: This study aimed to clarify whether work-related adverse events in cases involving compensation for mental disorders and suicide differ by sex and industry using a database containing all relevant cases reported from 2010 to 2014 in Japan. Methods: A total of 1362 eligible cases involving compensation for mental disorders (422 females and 940 males) were analyzed. Results: Among males, 55.7% of cases were attributed to "long working hours." In both sexes, the frequencies of cases attributed to "long working hours" and other events differed significantly by industry. Among cases involving compensation for suicide, 71.4% were attributed to "long working hours." Conclusions: The frequency distribution of work-related adverse events differed significantly by sex and industry. These differences should be taken into consideration in the development of industry-specific preventive measures for occupational mental disorders.